The Crohn's disease-associated adherent-invasive Escherichia coli strain LF82 replicates in mature phagolysosomes within J774 macrophages - Marie-Agnès Bringer; Anne-Lise Glasser; Ching‐Hsuan Tung; Stéphane Méresse; Arlette Darfeuille-Michaud (2005)
Adherent-invasive Escherichia coli (AIEC) bacteria isolated from Crohn's disease patients are able to extensively replicate within macrophages in large vacuoles. The mechanism by which AIEC bacteria survive within phagocytic cells is unknown. This report describes the maturation of AIEC LF82-containing phagosomes within J774 macrophages. LF82-containing phagosomes traffic through the endocytic pathway as shown by the sequential acquisition and loss of EEA1 and Rab7 and by accumulation of Lamp-1, Lamp-2 and cathepsin D. We demonstrated that AIEC LF82-containing phagosomes mature into active phagolysosomes where bacteria are exposed to low pH and to the degradative activity of cathepsin D. Finally, we showed that an acidic environment is necessary for replication of AIEC LF82 bacteria within J774 macrophages. Thus, evidence is provided that AIEC LF82 bacteria do not escape from the endocytic pathway but undergo normal interaction with host endomembrane organelles and replicate within acidic and cathepsin D-positive vacuolar phagolysosomes.